Barriers and Facilitators That Influence Providers' Ability to Educate, Monitor, and Treat Substance Use in First-Episode Psychosis Programs Using the Theoretical Domains Framework. (May 2021) - Oluwoye, Oladunni; Fraser, Elizabeth
In this qualitative study, we explore providers' experiences with addressing substance use among individuals with first-episode psychosis (FEP) enrolled in coordinated specialty care (CSC) programs. Three focus groups were conducted with 24 providers from CSC programs for FEP in Washington. Questions were focused on barriers and facilitators to addressing substance use using the Theoretical Domains Framework (TDF) as a guide. Thematic analysis was used to code all transcripts. Identified TDF domains were then mapped onto the COM-B (Capability, Opportunity, Motivation, Behavior) intervention functions and behavior change techniques. Seven theoretical domains were identified as the most relevant to addressing substance use: "Knowledge, " "Skills, " "Environmental Context and Resources, " "Social Influences, " "Social and Professional Role and Identity, " "Beliefs about Capabilities, " and "Reinforcement." The use of the TDF provides a framework to explore barriers and facilitators for targeting substance use and suggestions for behavior change techniques when considering implementation of evidence-based strategies to enhance CSC models.